Reliability analysis of subjectively graded real-image pterygium based on its translucence appearance between two experienced clinicians preliminary report - Hilmi, Mohd Radzi; Mohd Kamal, Khairidzan; Ithnin, Mohd. Hafidz (2019)
This study aimed compares the reliability of subjectively graded real-image pterygium based on its translucence appearance between experienced clinicians. Thirty (30) primary pterygium images from 30 pterygium patients were captured in a standardized magnification, illumination and formatting setting as previously described. All images were projected using PowerPoint presentationTM on liquid crystal display (LCD) monitor with standard resolution. Two experienced clinicians act as a grader and grade all images based on reference images provided. For reliability testing, intra-grader assessment was repeated twice with different sequence at least a month apart between each session. Both clinicians were given a set of 30 randomized pterygium images for all sessions. Reliability testing were evaluated using paired T-test and independent T-test. Descriptive analysis revealed observer 1 obtained mean grade of 2.33 (SD = 0.758) and 2.30 (SD = 0.837) for session 1 and 2 respectively. Observer 2 obtained 2.30 (SD = 0.702) and 2.17 (SD = 0.791) for session 1 and 2 respectively. Paired T-test results showed the difference for both observers were not statistically significant for both observer 1 and 2 (P = 0.662 and P = 0.293) respectively. Reproducibility testing using Independent T-test results showed the difference between observers was not statistically significant (P = 0.769). Subjectively graded pterygium clinical grading based on its translucence appearance was repeatable and reproducible. These findings could serve as basis for future work on to evaluate performance of pterygium clinical grading based on its morphology with different level of experience and larger number of samples.